Diasporic foodways and intersectionality in Chenta Tsai Tseng's Arroz tres delicias. - Kim, Yeon-Soo (Journal of Spanish Cultural Studies, 2022)
This article examines how Chenta Tsai Tseng engages with Chinese diasporic foodways to construct their identity as a racialized migrant subject. Tsai's memoir, Arroz tres delicias, uses the iconic Chinese dish as a metaphor for those who have had to survive by being creative, versatile and adaptable in limiting and oppressive diasporic conditions. Tsai also delves into how the popular dish was improvised rather than replicating a traditional recipe, providing a strategy to disidentify with and challenge Asian stereotypes. Tsai notes that Chinese culinary references are often used to racialize this minority community, whether to provoke social anxiety against them or to fetishize them. In the memoir, Tsai's reflections on their own experience of romantic relationships corroborates how their Asian race conditions their sexual objectification, which makes their identity intersectional. Tsai shifts the debate regarding the identity of Spaniards of Chinese descent from nation-states to transnational alliances, and from binaries to infinite, situational potentials. In contrast, Chinese Spanish cultural productions before Tsai, including Susana Ye's documentary Chiñoles y bananas and Quan Zhou Wu's graphic novel Gazpacho agridulce, have defied the Spanish xenophobia and discrimination against Asians by emphasizing the cultural differences between generations. Tsai's turn to intersectionality opens up the possibility of envisioning identity through an alternative history and a sense of belonging. At the same time, it presents a model for antiracist activism in solidarity with other oppressed groups. Both as a theory and praxis, intersectionality underpins ethical and affective affiliations in Tsai's identity, art and activism.